2016
DOI: 10.1039/c5cp07174g
|View full text |Cite
|
Sign up to set email alerts
|

Well-aligned Nd-doped SnO2 nanorod layered arrays: preparation, characterization and enhanced alcohol-gas sensing performance

Abstract: Well-oriented neodymium doped SnO2 layered nanorod arrays were synthesized by a substrate-free hydrothermal route using sodium stannate and sodium hydroxide at 210 °C. The morphology and phase structure of the Nd-doped SnO2 nanoarrays were investigated by X-ray powder diffraction spectroscopy, scanning electron microscopy, transmission electron microscopy, Raman scattering spectroscopy, X-ray photoelectron spectroscopy and the BET method. The results demonstrated that the Nd-doped SnO2 layered nanorod arrays s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 64 publications
1
24
0
Order By: Relevance
“…In this experiment, the MoO 3 nanorods showed almost the same molecule-surface bonding force, but the bulk MoO 3 , such as the dense seed layer, might possess a different molecule-surface bonding force because the surface potential energy of nanorods may higher than that of the bulk layer, [47] as seen in Figure S3 (Supporting Information). Because the lower surface potential energy results in a stronger bonding force between the oxide surface and gas molecules, the desorption ability will be weak when exposed to the oxygen gas during the recovery process, which suggests that recovery time may be delayed in the dense seed layer compared with that of the nanorods.…”
Section: Resultsmentioning
confidence: 93%
“…In this experiment, the MoO 3 nanorods showed almost the same molecule-surface bonding force, but the bulk MoO 3 , such as the dense seed layer, might possess a different molecule-surface bonding force because the surface potential energy of nanorods may higher than that of the bulk layer, [47] as seen in Figure S3 (Supporting Information). Because the lower surface potential energy results in a stronger bonding force between the oxide surface and gas molecules, the desorption ability will be weak when exposed to the oxygen gas during the recovery process, which suggests that recovery time may be delayed in the dense seed layer compared with that of the nanorods.…”
Section: Resultsmentioning
confidence: 93%
“…It is also worth noting that the increase in α value is highly pronounced in the 1.1 eV to 2.2 eV and 3.7 eV to 5.13 eV regions. The plot of the (αE) 2 vs. E reflects one region of variation that permitted determining the direct allowed transitions energy band gap E g of the neodymium tin oxide pyrochlore in accordance with the equation:…”
Section: Resultsmentioning
confidence: 99%
“…These nanorods were found to exhibit * E-mail: atef.qasrawi@atilim.edu.tr excellent features for alcohol gas sensing. It was suggested that the Nd-doped SnO 2 nanoarray sensors can be regarded as a promising candidate for detection of alcohol traces in environmental gas monitoring [2]. In addition, high responsivity of neodymium tin oxide pyrochlore to ion irradiation designates it as a promising material for disposal of nuclear waste [3].…”
Section: Introductionmentioning
confidence: 99%
“…Mishra et al 9 described Cudoped SnO 2 nanoparticles, which were synthesized by a coprecipitation method, and were then investigated as a formaldehyde sensing material. The 1.5 wt% Cu-doped SnO 2 showed a selective high response ($80%) to 50 ppm concentration of formaldehyde at 200 C. Qin et al 15 prepared Nd-doped SnO 2 nanorods by a substrate-free hydrothermal route of using sodium stannate and sodium hydroxide at 210 C. The Nddoped SnO 2 nanorods with an optimized Nd doping level of 3.0 wt% exhibited an excellent sensing response toward alcohol at 260 C. Li et al 2 demonstrated Cu 2+ /Au co-doped SnO 2 nanobers by electrospinning method, which were used to detect acetylene (C 2 H 2 ) at 160 C.…”
Section: Introductionmentioning
confidence: 99%
“…14 The sensing properties of a gas sensor are greatly inuenced by the microstructures, grain size, morphologies, and temperature. 15,16 SnO 2 materials have been prepared with different structures, 17 such as nanotubes, 18 nanorods, 19 nanosheets, 20 nanobers, 21 hollow spheres, 22 hierarchical owerlike nanostructures, 23 hollow porous microcubes, etc. [24][25][26][27][28] With the deepening of the research, it is found that the gas sensing properties of the SnO 2 -based composite materials are much higher than those of pure SnO 2 .…”
Section: Introductionmentioning
confidence: 99%